DETERMINASI SENJANGAN ANGGARAN - Anggita Nurindah Sari, - (2019)
This research is using quantitative study aimed to see whether there are influence of participatory budgeting and information asymmetry on the budgetary slack. This study was conducted on 20 SKPD in the Tangerang City Regional Government, with purposive sampling method. Data collected using by questionnaire. The number of respondents are 79 people that consisting of Head and members of sub financing and planning departments. The data analysis technique used are Multiple Linear Regression Analysis with SPSS (Statistical Product and Service Solutions) version 23 and MSI (Method of Succesive Interval) analysis tools with a significance level of 5% (a = 0,05). The result of these tests indicate that (1) there is a significance influence of participatory budgeting on the budgetary slack, and (2) there is a significance influence of information asymmetry on the budgetary slack.